Development of ipsilateral chest wall spindle cell carcinoma in a patient with invasive ductal breast carcinoma during postoperative adjuvant therapy: A case report. Issue 19 (May 2018) - Li, Kaifu; Kang, Hua; Wang, Yajun; Hai, Tao; Wang, Bixiao
Abstract: Rationale: Metaplastic breast carcinoma (MBC) is rare subtype of breast carcinoma and is regarded as ductal carcinoma that undergoes metaplasia into a glandular growth pattern. Spindle cell carcinoma (SPC) is a subtype of MBC with a predominant spindle cell component. Patient concerns: The patient was a 52-year-old female with invasive ductal breast carcinoma who underwent a modified radical mastectomy and an axillary node dissection. A new lump was observed underneath the surgical site between the pectoralis major and pectoralis minor muscles 45 days after the patient underwent sequential postoperative chemotherapy and radiotherapy. Diagnoses: It was speculated that the new lesion had developed during postoperative adjuvant therapy. And the new lesion was regarded as a recurrence. Interventions: We performed a wide dissection of the tumor with negative margins. The pathology of the tumor indicated SPC. Then, the patient received chemotherapy and demonstrated a poor response. Outcomes: Local recurrence and pulmonary metastasis developed shortly afterwards, and the patient succumbed to the disease within 5 months. Lessons: Local recurrence with metaplastic SPC transformed from invasive ductal breast carcinoma during postoperative chemotherapy and radiotherapy is rare. The failure of subsequent chemotherapy and the progression of disease indicate the aggressive nature of SPC and its decreased sensitivity to chemotherapy and radiotherapy. Further studies must be performed to improve the prognosis of these patients.